Evaluasi Kebijakan Pemungutan Retribusi Parkir Berlangganan Kota Mojokerto - Aditya Dwi Purnantoro; Dyah Lituhayu (Journal of Public Policy and Management Review, 2019)
Subscription parking retribution are payments for parking fees that must be paid by the owner of a motorized vehicle registered at the SAMSAT Office in Mojokerto City for a period of 1 (one) year in which payment is made in conjunction with the tax payment of the vehicle concerned. The purpose of the subscription parking retribution policy is contained in the Mojokerto Mayor Regulation No. 7 of 2010 is to increase PAD from the regional retribution sector and to improve parking services to the public. However, in its implementation despite being able to increase PAD in Mojokerto City significantly the parking fee retribution policy has not been able to provide maximum parking services. The purpose of this study was to determine the process of implementing a subscription parking retribution policy and to find the factor of implementing a subscription parking retribution policy did not run optimally. This type of research is descriptive research using qualitative methods. The results showed that the input indicators, process indicators and supervisory indicators that were evaluated were factors for the implementation of the subscription parking retribution policy not running optimally. Among them are aspects of human resources, retribution collection methods, effectiveness and efficiency, supervisory resources, intensity of supervision, and aspects of the method of taking corrective actions. Recommendations that can be given are increasing the standard of recruitment of parking officers, giving freedom to the public to choose whether to use retribution or not, increasing the number of supervisory resources, increasing the intensity of supervision, and improving supervision methods by increasing coordination with parking officers in the field.